2020
DOI: 10.22271/chemi.2020.v8.i1q.8422
|View full text |Cite
|
Sign up to set email alerts
|

Studies on genetic correlation and path coefficient analysis of blackgram (<em>Vigna mungo </em>[l.] Hepper) genotypes under rainfed situations

Abstract: The experiment was conducted under rainfed condition at Agricultural Research Station, Madhira during early rabi 2016 using 35 blackgram germplasm lines along with four checks. Estimation of variation, phenotypic and genotypic correlations along with path analysis was calculated for the material under study. Days to maturity and plant height had positive significant correlation with number of clusters per plant, number of pods per plant, 100 seed weight, seed yield per plant and seed yield (kg/ha). Number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Yield per plant also showed significant to highly significant positive correlation with plant height (0.453**), number of clusters per plant (0.331**), number of pods per cluster (0.478**), number of pods per plant (0.468**), pod length (0.297*), pod weight (0.463**), and seeds per pod (0.517**). These results are in close conformity with the finding of Rasel Miah et al, (2016) [7,9] , C R. Konda et al, (2018) [12] , Sridhar et al, (2019) [17] , Shalini et al, (2019) [19] and Bhanu Pratap et al, (2019) [18] . Negative significant association exhibited by pod length (-0.225* ) with the yield per plot.…”
Section: Genotypic Correlationsupporting
confidence: 90%
See 1 more Smart Citation
“…Yield per plant also showed significant to highly significant positive correlation with plant height (0.453**), number of clusters per plant (0.331**), number of pods per cluster (0.478**), number of pods per plant (0.468**), pod length (0.297*), pod weight (0.463**), and seeds per pod (0.517**). These results are in close conformity with the finding of Rasel Miah et al, (2016) [7,9] , C R. Konda et al, (2018) [12] , Sridhar et al, (2019) [17] , Shalini et al, (2019) [19] and Bhanu Pratap et al, (2019) [18] . Negative significant association exhibited by pod length (-0.225* ) with the yield per plot.…”
Section: Genotypic Correlationsupporting
confidence: 90%
“…Number of clusters per plant showed a highly significant positive correlation with number of pods per plant (0.752**), number of pods per cluster (0.285*), and pod weight (0.465**). These results were in consonance with Isha Parveen et al, (2011) [1] , Gowsalya et al, (2016) [10] , Mohan Lal et al, (2018) [13] and Sridhar et al, (2019) [17] which indicating that the selection of plants with more number of clusters may increase the number of pods per plant, pods per cluster and pod weight. The magnitude of genotypic correlations of all characters were higher than phenotypic correlations indicating the prominence of additive x additive gene action (Falconer 1981) and strong inherent genetic association between traits and less effect of environment on genotypes.…”
Section: Genotypic Correlationsupporting
confidence: 82%
“…Based on GCV, PCV, h 2 and GG, traits such as days to initial flowering, days to 80% maturity, days to initial maturity, days to 50% flowering, seed weight and seeds/pod were found highly suitable for blackgram breeding programs (Table 1). As source of the germplasm and population size varies among other studies, results also varies to some extent but trends remain similar (Ghafoor et al 2001;Ghafoor and Ahmad 2005;Punia et al 2014;Sridhar et al 2020). Simple selection of promising accessions listed in Table 4 for these traits and their utilization in the breeding programs can have significant impact on the crop improvement.…”
Section: Discussionmentioning
confidence: 82%
“…with better agronomical traits. This is primarily because of inadequate utilization of variability in blackgram breeding programs (Gupta and Parihar 2015;Sridhar et al 2020;Gupta et al 2021). The pedigree analysis of blackgram varieties indicates that 30% of the varieties are developed utilizing only ten parents, of which T-9 is the most frequently used (Gupta and Parihar 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Path coefficient analysis supports the assessment of each variable's impact on the resultant variable directly and indirectly by partitioning the genetic correlation coefficients (Ashfaq et al, 2014;Sridhar et al, 2020;Adnan et al, 2021). Previously, Chauhan et al (2007) performed path analysis and identified the number of pods per plant, followed by number of seeds per pod, and 100-seed weight were the chief direct contributing characteristics toward the phenotypic expression of seed yield per plant.…”
Section: Discussionmentioning
confidence: 99%